The functional state of athletes who have undergone coronavirus infection (covid-19) - Zaborova, V.; Lazareva, I.; Kryuchkova, K.; Popova, C.; Rybakov, V.; Shestakov, D.; Bonavolontà, V.; Guidetti, L.; Zimatore, G. (Sports Medicine and Health Science, 2025)
This study aimed to investigate the energy supply of athletes, who had a mild form of coronavirus infection (COVID-19) under cycling ergometric load (CEL) to substantiate the timing of recovery, as well as to determine the volume and intensity of physical activity. Eighty-seven athletes aged from 18 to 28 years old, involved in cyclic sports, were examined. Group I consisted of 52 athletes with COVID-19, and group II consisted of 37 healthy self-isolating athletes. In addition to the comprehensive examination, the tested athletes underwent special examinations: the study of diagnostic material using methods of nucleic acid amplification, spirography and spiroergometry, electrocardiography (ECG), and CEL. The results of athletes from both groups did not differ significantly (p > 0.5) in the 1st, 2nd, and 3rd examinations. The second examination revealed a discrepancy between functional reserves and the load performed, as evidenced by the difference in the recovery rate of most indicators, the results of the third examination in the long-term period (6 months) showed that the athletes of the first group did not have any violations of the parameters of the respiratory function (RF) and cardiovascular system at rest, after performing CEL, as well as in the recovery period. The results suggest that the full resumption of training loads and participation in competitions are possible only with the complete normalization of the functional state of the cardiorespiratory system. The most informative indicators are: minute ventilation (VE), heart rate (HR), oxygen pulse (OP), and coefficient of oxygen utilization (COU).